1984
DOI: 10.1021/ac00265a003
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption mass spectrometry with thermospray sample deposition for determination of nonvolatile biomolecules

Abstract: A new laser desorption mass spectrometer has been Interfaced to a liquid chromatograph using a moving stainless steel belt. Samples are sprayed on-line onto the belt under partial vacuum with a thermospray vaporizer. These samples are transported through a differentially pumped vacuum lock and ionized In the source of the mass spectrometer with 45 ns, 10s W/cm2 laser pulses from a Q-swltched Nd:YAG laser. Data on the performance of this new LC/LDMS are presented for several classes of nonvolatile, thermally la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Vestal and coworkers reported that non-resonant desorption/ionization of non-volatile compounds led to a dominance of alkali cationized species over protonated ones. 27,28 In practical MALDI experiments, the two processes usually coexist and compete. The competition between protonation and cationization is evident in the so-called 'matrix suppression effect'.…”
Section: Introductionmentioning
confidence: 99%
“…Vestal and coworkers reported that non-resonant desorption/ionization of non-volatile compounds led to a dominance of alkali cationized species over protonated ones. 27,28 In practical MALDI experiments, the two processes usually coexist and compete. The competition between protonation and cationization is evident in the so-called 'matrix suppression effect'.…”
Section: Introductionmentioning
confidence: 99%
“…Namely: fast atom bombardment (FAB) [1], field desorption (FD) [2], laser desorption (LD) [3], plasma desorption mass spectrometry (PDMS) [4] and secondary ion mass spectrometry (SIMS) [5]. In spite of the significant improvement and extended applicability of these methods they all suffer of the same limitation derived from the fact that both desorption and ionisation cannot be separately optimised, which, obviously, may be critical for many real applications.…”
mentioning
confidence: 99%
“…Even considered that the terms "thermal" and "equilibrium process" are used with somewhat different meanings by different authors, the fundamental questio remains. Observation of "non volatile", large organic parent molecular ions with relative molecular masses above 1000 [18,21,22,29,31,36)and often very limited fragmentation supports the notion of a nonequilibrium process.Ver little is on the other hand known about the true volatility of most substances investigated and some of the improvements in the range of detected large ions also result from increased sensitivities of the instruments used. The prolonge ion emission over tens of microseconds as reported by COTTER(17, 18J, on the other hand, seems to rather support a therma1 model.…”
Section: Mechanisms Of Laser Desorptionmentioning
confidence: 72%
“…LD had a rather slow start, but considering the limited number of investigators, progress has been quite remarkable nonetheless. A variety of bioorganic molecules with relative molecular masses in the range of 1000-2000 have been detected with all the different techniques [18,21,22,29,31,36] . Fig.…”
Section: Status and Outlookmentioning
confidence: 99%